(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
The problem of scheduling jobs on a single machine to minimize the weighted sum of squares completion time is considered .Al-Salihi used a branch and bound method to minimize the weighted sum of squares completion time. In this research we discuss and apply some known local search methods , namely the adjacent pairwise interchange method (APIM) and descent method (DM) . The performance of local search methods can be tested on large class of test problems.